Prediction Model of Flight Plan Departure Procedure Based on Extra-Tree - Zixuan, Wu; Qisong, Hu; Sheng, Yu; Kaiye, Gao (IEEE Joint International Information Technology and Artificial Intelligence Conference (ITAIC ... ) (Online), 2022)
Flight plan is an important basis for flight operation. In order to improve the fuel economy and reduce unnecessary fuel consumption, it is necessary to accurately predict the departure procedure of the flight plan, so as to determine the trip refuel of the flight. Using artificial intelligence algorithm, this paper constructs a flight departure procedure prediction model by analyzing historical and real-time flight plan, risk control, weather and other data, and integrating dispatchers' business knowledge and experience. The experimental results based on historical data show that the model can accurately predict the departure procedures under multi-complex scene, with high robustness and better performance. The model is being applied in the dispatch scenario of X airlines to assist dispatchers to make decisions based on data.